KONGSI KEMATIAN AS AN ECONOMIC SUPPORT INSTITUTION IN MINANGKABAU SOCIETY: AN ISLAMIC ECONOMIC LAW PERSPECTIVE - Zuhri Arif; Rahmayanti Rahmayanti; Vovi Arvani; Syah Wardi (Journal Analytica Islamica, 2026)
Kongsi kematian as one of the results of Minangkabau society's wisdom has contributed greatly in various aspects of life. Unfortunately, there is still very little in-depth scientific research on kongsi kematian. This study aims to conduct a comprehensive examination of kongsi kematian from the perspective of Islamic economic law. The study was conducted using a qualitative approach with a library research method. The literature was identified, compared, analyzed, and synthesized to answer the research questions. The research results show that the practice of kongsi kematian plays a significant role in economically supporting the Minangkabau community when they experience the misfortune of death. From the perspective of Islamic economic law, it is concluded that the economic practices carried out within the kongsi kematian system meet the requirements of Islamic economic transactions under the wadi’ah category. Starting from the person who entrusts and the person entrusted, the goods that are entrusted, as well as the offer and acceptance, already meet the criteria of Sharia law. Therefore, future researchers are encouraged to conduct more comprehensive studies on the implementation of kongsi kematian on a broader scale.